Sod1 deficiency in mouse oocytes during in vitro maturation increases chromosome segregation errors with a reduced BUBR1 at kinetochore - Mitsuru Nago; Masumi Yanai; Mika Ishii; Yasuko Sato; Kazuharu Odajima; Naoko Kimura (Reproductive Medicine and Biology)
Abstract Purpose This study aimed to investigate the molecular mechanisms associated with chromosome segregation errors caused by intrinsic oxidative stress during in vitro oocyte maturation (IVM) using oocytes from Sod1‐deficient (Sod1KO) mice. Methods Ovulated or in vitro matured cumulus‐cells oocyte complexes (COCs) were collected from wild‐type (WT) and Sod1KO mice and evaluated chromosome alignment, chromosome segregation, meiotic progression, and BUBR1 and REC8 protein expression levels. Results In 21% O2 IVM, the Sod1KO had significantly higher frequencies of chromosome misalignment and segregation errors compared to the WT, and they also reached Germinal Vesicle Break Down (GVBD) and M I stages peak earlier and showed a shorter M I stage residence time compared to the WT. These changes were associated with a decrease in the recruitment of BUBR1 to kinetochores at M I stage, but there were no differences in the expression of REC8 between the two genotypes. Furthermore, the addition of L‐ascorbic acid (AsA) or N‐acetyl‐L‐cysteine (NAC) during IVM reduced the frequency of chromosome segregation errors in Sod1KO oocytes. Conclusions Oxidative stress caused by Sod1 deficiency during IVM impairs the spindle assembly checkpoint function due to a decrease in the recruitment of BUBR1 to M I stage kinetochores, leading to abnormalities in meiotic progression and chromosome segregation.